A multifunctional chitosan hydrogel dressing for liver hemostasis and infected wound healing. (1st September 2022) - Yang, Erkang; Hou, Wen; Liu, Kun; Yang, He; Wei, Wenying; Kang, Haifei; Dai, Honglian
Abstract: For the treatment of infected bleeding wounds, we compounded methacrylate anhydride dopamine (DAMA) and Zn-doped whitlockite nanoparticles (Zn-nWH) into methacrylate anhydride quaternized chitosan (QCSMA) to obtain a multifunctional hydrogel dressing (QCSMA/DAMA/Zn-nWH) with hemostasis, disinfection and wound healing promotion. QCSMA/DAMA/Zn-nWH exhibited good adhesion (0.031 MPa) and DPPH scavenging ability (94%), favorable biocompatibility (hemolysis ratio < 2%, no cytotoxicity), and showed a low BCI value (< 13%) in vitro coagulation test and could activate coagulation pathway. In addition, QCSMA/DAMA/Zn-nWH had excellent hemostatic effect (129 ± 22 s, 27 ± 5 mg) in vivo compared with the control (571 ± 15 s, 147 ± 31 mg) and CCS (354 ± 27 s, 110 ± 46 mg). Meanwhile, QCSMA/DAMA/Zn-nWH showed excellent antibacterial properties (> 90% against S. aureus and E. coli ) and could promote collagen deposition, reduce inflammatory expression and promote wound healing. All results indicate that these multifunctional hydrogel dressings have great potential in clinical hemostasis and anti-infection healing. Graphical abstract: Preparation of QCSMA/DAMA/Zn-nWH hydrogel dressing through mixing the methacrylate anhydride quaternized chitosan (QCSMA), methacrylate anhydride dopamine (DAMA) and Zn-doped whitlockite nanoparticles (Zn-nWH) via photo-polymerization and the coordination of metal ions with the catechol group of dopamine. The hydrogel dressing has excellent adhesion antibacterial and antioxidation properties, which can quickly achieve incompressible liver hemostasis, and promote the infected full-thickness skin defect wound healing. Unlabelled Image